2017
DOI: 10.1038/s41598-017-17292-3
|View full text |Cite
|
Sign up to set email alerts
|

Stationary Rossby waves dominate subduction of anthropogenic carbon in the Southern Ocean

Abstract: The Southern Ocean has taken up more than 40% of the total anthropogenic carbon (Cant) stored in the oceans since the preindustrial era, mainly in subantarctic mode and intermediate waters (SAMW-AAIW). However, the physical mechanisms responsible for the transfer of Cant into the ocean interior remain poorly understood. Here, we use high resolution (1/10°) ocean simulations to investigate these mechanisms at the SAMW-AAIW subduction hotspots. Mesoscale Stationary Rossby Waves (SRWs), generated where the Antarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 59 publications
2
37
0
Order By: Relevance
“…1) on the nutrients and other tracers is poorly understood. However, recent work has shown that the upwelling and subduction in the Southern Ocean is controlled by the complex interactions between the frontal jets, large bathymetric features, and surface winds 45,48,49 . As such, the upwelling of nutrients and subduction of CO 2 into the ocean interior is localized to regions where fronts interact with bathymetry [49][50][51] .…”
Section: Fronts Biogeochemistry and Ecosystems In The Southern Oceanmentioning
confidence: 99%
“…1) on the nutrients and other tracers is poorly understood. However, recent work has shown that the upwelling and subduction in the Southern Ocean is controlled by the complex interactions between the frontal jets, large bathymetric features, and surface winds 45,48,49 . As such, the upwelling of nutrients and subduction of CO 2 into the ocean interior is localized to regions where fronts interact with bathymetry [49][50][51] .…”
Section: Fronts Biogeochemistry and Ecosystems In The Southern Oceanmentioning
confidence: 99%
“…More generally, in the eddy-induced circulation, a steady state cross-frontal circulation can occur where Eliassen-Palm flux divergence is nonzero (e.g., Haynes et al, 1991). This eddy-induced circulation is different from the cross-frontal circulation discussed by Sekma et al (2013) and Langlais et al (2017), wherein the circulation is driven by strong bottom currents flowing over the sloping topography affecting the Fawn Trough and Kerguelen Plateau.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This, in turn, affects oceanic carbon sequestration. Second, the meltwater carries bioavailable iron to the Southern Ocean -which affects oceanic primary productivity and the associated export of organic carbon to depth (Grotti et al, 2005;Lannuzel et al, 2008Lannuzel et al, , 2010Raiswell et al, 2008;Smith et al, 2007;Smith and Nelson, 1986;van der Merwe et al, 2009). Figure 34 shows that the simulated Antarctic continental shelf bottom water (ASBW) changes its temperature in re- Figure 26.…”
Section: Wind-induced Anomalies In Antarctic Continental Shelf Bottommentioning
confidence: 99%